The making of transparent soap based on olive oil with the addition of white tea extract - Widyasanti, Asri; Rohani, Jayanti Mega (Jurnal Penelitian Teh dan Kina, 2017)
Tea is a popular drink in the world. Types of tea which is rarely used is white tea. Besides consumed as a beverage, white tea can also be used in extracted form. White tea extract contains polyphenols compound, particularly catechins that can be used as an antibacterial. One of white tea extract uses that can be added to production of olive oil transparent soap based. This study aimed to determine the process of transparent soap production, looking for the best concentration of white tea extract, determine the characteristic and quality of transparent soap, and look for the extend of inhibition zone of Staphylococcus aureus in transparent soap. The treatments given in this research were the concentration of white tea extract 1% (w / v) with the addition of A (control soap) = 0% (w / w), B = 0,5% (w / w), C = 1,0% (w / w), and D = 1,5% (w / w) of 300 grams of soap bases. Transparent soap characteristics observed were physical-chemical properties, antibacterial and organoleptic test. The analysis showed that all transparent soap baths complied the SNI 06-3532-1994 requirements of solid soap, except the water content and evaporated substance and the amount of fatty acids. The best result of this research was soap with treatment B (with 0,5% (w/w) extract addition), which was chosen based on organoleptic test (such as aroma, hardness and foam quantity) and Indonesian National Standard (SNI) qualities of solid soap with best result in unsaponified fraction test, hardness, and foam stability.